The 1997–1998 El Niño event recorded by a stalagmite from central China. (10th September 2018) - Liu, Shuhua; Peng, Xiaotao; Chen, Qiong; Qin, Shijiang; Zhao, Jianxin; Feng, Yuexing; Luo, Shangde; Zhou, Houyun
Abstract: The El Niño-Southern Oscillation (ENSO) is one of the most important oceanic and atmospheric phenomena that cause global climate variations. In this study, we reported a stalagmite δ 18 O record from Shizi cave in central China, which clearly shows a prominently positive variation during 1997–1998 CE. This δ 18 O variation correlates well with a thinner annual layer that indicates a decrease in the growth rate, possibly due to a reduction of the rainfall amount near our study site caused by the 1997–1998 El Niño event. This hypothesis is supported by a comparison of the variations of the rainfall amount near the study site in terms of the southern oscillation index (SOI) for the last 60 years, which indicates that almost all of the El Niño events lead to a reduced rainfall amount. The results suggest that speleothems deposited in central China may potentially reflect El Niño activity.